Atomic‐scale microstructure of Hf2Al4C5 ceramic synthesized by spark plasma sintering. Issue 7 (30th March 2017) - Song, Kepeng; Zhang, Hui; Du, Kui; Qi, Dongqing; Chen, Houwen; Wang, Xiaohui; Nie, Jian‐Feng; Ye, Hengqiang
Abstract: A layered ternary carbide phase, Hf2 Al4 C5, was successfully synthesized by spark plasma sintering method. Detailed (atomic‐scale) microstructure of the ternary carbide was investigated by aberration‐corrected scanning transmission electron microscopy and atomic‐resolution energy dispersive X‐ray spectroscopy. Hf2 Al4 C5 crystal grains have elongated morphologies and are characterized with a high density of stacking faults with the insertion of additional (Al4 C3 ) or (HfC) units. Periodic stacking of Hf2 Al4 C5 and HfAl4 C4 units along the [0001] direction is frequently observed in the Hf2 Al4 C5 crystal, and it leads to the formation of Hf4 Al12 C13, which consists of 2/3 Hf2 Al4 C5 unit cell and 1/2 HfAl4 C4 unit cell. In addition, Z‐shaped planar defects are observed in Hf2 Al4 C5 grains, and the formation mechanism of the Z‐shaped defects was proposed as blocking effects of the Hf diffusion in Al4 C3 by pre‐existing {1‐101} pyramidal stacking faults in Al4 C3.